2012
DOI: 10.1164/rccm.201108-1545oc
|View full text |Cite
|
Sign up to set email alerts
|

IL-18 Induces Emphysema and Airway and Vascular Remodeling via IFN-γ, IL-17A, and IL-13

Abstract: Rationale: Chronic obstructive pulmonary disease (COPD) is characterized by chronic inflammation, alveolar destruction, and airway and vascular remodeling. However, the mechanisms that lead to these diverse alterations have not been defined. Objectives: We hypothesized that IL-18 plays a central role in the pathogenesis of these lesions. Methods: We generated and characterized lung-specific, inducible IL-18 transgenic mice. Measurements and Main Results: Here we demonstrate that the expression of IL-18 in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
78
1
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 89 publications
(88 citation statements)
references
References 63 publications
(86 reference statements)
7
78
1
2
Order By: Relevance
“…Moreover, there was higher expression of il18 in BALB/cJ relative to C57BL/6J mice, both at baseline and after elastase administration. Mice overexpressing either IFN-␥ or IL-18 specifically in the adult lung displayed an emphysema-like phenotype accompanied by high levels of proteases such as MMP-12 and cathepsins in prior studies (40,84). In addition, it was also reported that IL-17A-deficient mice develop less pulmonary inflammation accompanied by a reduction in the severity of emphysema after elastase exposure (43).…”
Section: Discussionmentioning
confidence: 92%
“…Moreover, there was higher expression of il18 in BALB/cJ relative to C57BL/6J mice, both at baseline and after elastase administration. Mice overexpressing either IFN-␥ or IL-18 specifically in the adult lung displayed an emphysema-like phenotype accompanied by high levels of proteases such as MMP-12 and cathepsins in prior studies (40,84). In addition, it was also reported that IL-17A-deficient mice develop less pulmonary inflammation accompanied by a reduction in the severity of emphysema after elastase exposure (43).…”
Section: Discussionmentioning
confidence: 92%
“…The increase of sputum MUC1 CT fragment in AECOPD was probably due to detachment of damaged epithelial cells carrying overexpressed MUC1 caused by background chronic inflammation plus a flare up of inflammation in acute exacerbation, since hallmark features of COPD include obstructive bronchiolitis and emphysema parenchymal destruction (21,22). In order to maintain the epithelial integrity, the detachment of damaged cells from the monolayer results from extrusion effects by dedifferentiated ciliated cells (23).…”
Section: Discussionmentioning
confidence: 99%
“…These studies were among the first to imply a possible contributory role for inflammasome signaling and IL-1b responses in CS-induced airways inflammation (37). Targeted overexpression of the inflammasome-regulated cytokine, IL-18, in murine lungs resulted in widespread pulmonary inflammation, airway remodeling, and emphysematous lesions, suggesting a role for IL-18 in COPD pathogenesis (38).…”
Section: Inflammasomes In Airways Diseasesmentioning
confidence: 99%